2009
DOI: 10.1186/1471-2105-10-386
|View full text |Cite
|
Sign up to set email alerts
|

Identifying quantitative operation principles in metabolic pathways: a systematic method for searching feasible enzyme activity patterns leading to cellular adaptive responses

Abstract: BackgroundOptimization methods allow designing changes in a system so that specific goals are attained. These techniques are fundamental for metabolic engineering. However, they are not directly applicable for investigating the evolution of metabolic adaptation to environmental changes. Although biological systems have evolved by natural selection and result in well-adapted systems, we can hardly expect that actual metabolic processes are at the theoretical optimum that could result from an optimization analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 58 publications
0
49
0
Order By: Relevance
“…MCMC was also applied to different classes of metabolic pathways [467][468][469][470][471][472][473][474][475][476], the evolutionary development of different designs of enzyme systems and moiety-transfer cycles [477][478][479][480][481][482][483][484], bacterial growth phenomena [485], two-component sensing systems with and without bistable switches and hysteresis [387][388][389][390]475], a stress response system in yeast [486], higher plant systems [487], and even control systems for lymphocytes and their responses to antigens [462,463]. Puigjaner and colleagues compared MCMC for BST and metabolic control analysis (MCA; [488]).…”
Section: Design and Operation And The Methods Of Controlledmentioning
confidence: 99%
See 2 more Smart Citations
“…MCMC was also applied to different classes of metabolic pathways [467][468][469][470][471][472][473][474][475][476], the evolutionary development of different designs of enzyme systems and moiety-transfer cycles [477][478][479][480][481][482][483][484], bacterial growth phenomena [485], two-component sensing systems with and without bistable switches and hysteresis [387][388][389][390]475], a stress response system in yeast [486], higher plant systems [487], and even control systems for lymphocytes and their responses to antigens [462,463]. Puigjaner and colleagues compared MCMC for BST and metabolic control analysis (MCA; [488]).…”
Section: Design and Operation And The Methods Of Controlledmentioning
confidence: 99%
“…A different extension of methods for the discovery of design principles was the corresponding analysis of operating principles, where the focus is not so much on the structural design of systems, but on their operation in response to stimuli [76,77,380,484]. A recent review of design and operating principles can be found in [78].…”
Section: Design and Operation And The Methods Of Controlledmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the minlp.org problem GMA ethanol model CH [80,81], there are seven signomial terms with nonnegative variables natural to the model formulation; all seven participate in both a convex and concave direction:…”
Section: Adding Nonconvex Terms For Advanced Rltmentioning
confidence: 99%
“…The remaining terms are convex in one direction and concave in the other. The reinforcing exponential transformation, convex hulls, and RLT equations allow the MISO framework to solve GMA ethanol model CH [80,81] to a relative optimality tolerance of 1 × 10 −4 % in 1.1 CPU s.…”
Section: Adding Nonconvex Terms For Advanced Rltmentioning
confidence: 99%